Դրուզների կրոնաքաղաքական ուսմունքի առանձնահատկությունները - Արթուր Մելքոնյան (ՀՀ ԳԱԱ հրատ.)
The appearance of Druze religious doctrine takes place in the 10-11th centuries, and is connected with the name of Muhammad Ibn Ismail Ad-Darazi, and in some parts of Syria, that doctrine of Hamza Ibn Ahmad is spread, thet the Egyptian khalifa Al-Haqim Ibn Allah originating from the Fatima dynasty is the embodiment of God.
Keywords: Religion; Ethnic Groups and Races